Digital vector of Ukraine development: formation of national industry of oceanographic geospatial data - Shchyptsov, О.A. (Geofizicheskiy Zhurnal, 2021)
A step-by-step deployment of work on the creation of a national geospatial data infrastructure within the digital development of Ukraine is considered. The goals of mentioned infrastructure are as follows: provision of the open access to data, in particular the data and knowledge of scientific researches and observations; involvement of the national oceanographic scientific community in the global network of “big data”, further commercialization of research results, creation of innovations, digital products and services. The digital industry of oceanographic geospatial data is expected to become one of the components of the national digital geospatial data infrastructure. It will primarily cover the oceanography, considering the scale and complexity of hydrophysical processes in the oceans, the multifaceted impact and use of data for the sustainable development and economic activity; as well as conceptually modernize data production and disposal. The article presents an analysis of the Law on the National Infrastructure of Geospatial Data regarding the provisions that have to be fulfilled by the holders of oceanographic data. Considering that in accordance to the Law the national geospatial data infrastructure does not cover the entire array of collected oceanographic data, additional preparatory measures are proposed for the formation of a modern infrastructure and digital industry of oceanographic data. Creation of a modern digital industry of oceanographic data requires concerted efforts and consolidated actions of the state, scientific community, business entities and interested civil society. Its creation will ensure an appropriate level of participation and form a positive image of Ukraine in the framework of the United Nations Decade of Ocean Science for Sustainable Development (2021—2030).